ASPEK LEGAL PEMUNGUTAN BPHTB BERDASARKAN QANUN KOTA LHOKSEUMAWE NOMOR 04 TAHUN 2010 TENTANG BPHTB - NURFADHILLAH NURFADHILLAH (PREMISE LAW JURNAL, 2015)
After Law No. 28/2009 on State and Local Tax and Retribution was in effect, since 2011 BPHTB levying, which used to be the authority of the Central Government, has been shifted to Local Government of Districts/Towns. The law states that levying BPHTB tax in certain area should be stipulated in Perda (Regional Regulation) or Qanun. Based on this condition, Lhokseumawe City Administration issued Lhokseumawe Qanun No. 4/2010 in conjunction with the Mayor Regulation No. 30/2013. Law No. 28/2009 on State and Local Tax states that the levying system of payable BPHTB at Lhokseumawe should use self assessment system, but Qanun No. 4/2010 in conjunction with the Mayor Regulation No. 30/2013 states that the levying system of BPHTB uses official assessment system. The problems of the research were as follows: how about levying system of BPHTB at Lhokseumawe according to Qanun No. 4/2010, how about legal domicile of the Mayor Regulation No. 30/2013, and what obstacles occurred in levying BPHTB, based on Qanun No. 4/2010 at Lhokseumawe. Keywords: Collecting, BPHTB, Qanun